CATALYTIC PROPERTIES OF ACID-MODIFIED ALUMINOSILICATES IN GLYCEROL KETALIZATION WITH ACETONE - Davtian, Araksia; Levchenko, Olha; Yaremov, Pavlo; Kurmach, Mykhailo (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2026)
The catalytic properties of natural aluminosilicates from Ukrainian deposits modified with sulfuric acid were studied in glycerol ketalization with acetone. Bentonite (Bent, Dashukivske deposit), clinoptilolite (Cli, Sokyrnytske deposit) and trepel (Tr, Konoplianske deposit) were treated with sulfuric acid to increase their acidity and improve catalytic performance. The influence of catalyst loading, reaction temperature and glycerol:acetone molar ratio on glycerol conversion and initial rate of its consumption was investigated. It was found that catalytic activity strongly depends on structural, adsorption and acidic characteristics of aluminosilicates. The highest catalytic activity was observed for sulfuric acid-modified bentonite (H-Bent), which provided a maximum glycerol conversion of 81% at 45 °C, catalyst loading of 3 wt.% and glycerol:acetone molar ratio 1:25. H-Tr and H-Cli exhibited lower acti-vity, reaching 71% and 60% conversion, respectively, under the same conditions. The superior performance of H-Bent is associated with its higher specific surface area (243 m2/g), developed mesoporous structure and higher concentration of Brønsted and Lewis acid sites. Nitrogen adsorption-desorption analysis showed that all investigated samples belong to type IV isotherms, characteristic of micro- mesoporous materials. H-Bent had the highest total pore volume and mesopore surface area, while H-Cli contained a noticeable fraction of micropores. Pyridine adsorption studies revealed that H-Bent contains both Brønsted and Lewis acid sites of medium and high strength, whereas H-Tr and H-Cli are characterized mainly by weak and medium-strength Brønsted sites. Kinetic analysis demonstrated that the reaction order with respect to glycerol is close to one for H-Bent and two for H-Tr, indicating differences in rate-limiting step and reaction mechanism. The pseudo-Michaelis constants and maxi¬mum reaction rates were also determined, confirming the significantly higher catalytic efficiency of H-Bent compared to other investigated samples. Furthermore, the obtained results demonstrate that sulfuric acid-modified bentonite is a promising low-cost and environmentally friendly catalyst for glycerol valorization into cyclic ketals, which can be considered valuable fuel additives and intermediates for chemical industry.